GSK-3 as a novel prognostic indicator in leukemia. (August 2017) - Ruvolo, Peter P.
Abstract: While leukemias represent a diverse set of diseases with malignant cells derived from myeloid or lymphoid origin, a common feature is the dysregulation of signal transduction pathways that influence leukemogeneisis, promote drug resistance, and favor leukemia stem cells. Mutations in PI3K, PTEN, RAS, or other upstream regulators can activate the AKT kinase which has central roles in supporting cell proliferation and survival. A major target of AKT is Glycogen Synthase Kinase 3 (GSK3). GSK3 has two isoforms (alpha and beta) that were studied as regulators of metabolism but emerged as central players in cancer in the early 1990s. GSK3 is unique in that the isoforms are constitutively active. Active GSK3 promotes destruction of oncogenic proteins such as beta Catenin, c-MYC, and MCL-1 and thus has tumor suppressor properties. In AML, inactivation of GSK3 is associated with poor overall survival. Interestingly in some leukemias GSK3 targets a tumor suppressor and thus the kinases can act as tumor promoters in those instances. An example is GSK3 targeting p27Kip1 in AML with MLL translocation. This review will cover the role of GSK3 in various leukemias both as tumor suppressor and tumor promoter. We will also briefly cover current state of GSK3 inhibitors for leukemia therapy.